Developmentally appropriate instruction beliefs and teaching practices of parents of primary grade homeschooled children - Yusi, Jenny Lou Sol (2008)
This study attempted to investigate the parents' personal understanding and beliefs in teaching children and how children learn. It observed how parents' viewpoints align with the defined ideas of the National Association for the Education of Young Children and developmentally appropriate practices as a philosophy of instructional practice. Interviews and self-reported teachaing beliefs and practices were used in the study. Results show that the parent-teachers subscribe to a combination of two sets of beliefs - one more child-led, and the other is teacher-led. Their beliefs are strongly aligned with their self-reported practices. Parents believe that the combination approach creates a learning environment that combine active, child-initiated approaches with structured learning.